Spatial matching on the urban labor market: estimates with unique micro data - Marcin Wozniak (Journal for Labour Market Research, 2021)
In the paper, we investigate spatial relationship on the labor market of Poznan agglomeration (Poland) with unique data on job vacancies. We have developed spatial panel models to assess the search and matching process with a particular focus on spatial spillovers. In general, spatial models may provide different findings than regular panel models regarding returns to scale in matching technology. Moreover, we have identified global spillover effects as well as other factors that impact the job-worker matching. We underline the role of data on job vacancies: the data retrieved from commercial job portals produced much more reliable estimates than underestimated registered data.
Keywords: J23; J64; R12; E24; 330; Spatial matching function; Spatial correlation; Urban labor market